P1-S2.06 HIV, sexually transmitted infections, and risk behaviours among clients of sex workers in Guatemala - are they a bridge in HIV transmission?. (10th July 2011) - Sabidó, M; Lahuerta, M; Hernández, G; Montoliu, A; Gonzalez, V; Giardina, F; Monzón, J E; Pedroza, M I; Casabona, J; Guevara, R
Abstract : Background: Clients of female sex workers (FSW) are an important target group for HIV/STI prevention. This study aimed to estimate the prevalence of HIV and other sexually transmitted infections (STI) prevalence in clients examine their risk behaviours and evaluate their role as a bridge population in the spread of HIV/STI. Methods: Cross-sectional study conducted between 2008 and 2009 among 553 clients recruited through a two-stage convenient sample in commercial sex sites in the province of Escuintla, Guatemala. They were interviewed and tested for HIV and other STI. Bridge clients were defined as those who engaged in sex with both regular partners and FSWs but reported inconsistent condom use with FSWs whereas potential bridge as those reported consistent condom use with FSWs. Non-bridge clients engaged in sex with only FSWs. Multinomial and multivariable logistic regression models were used to identify risk factors associated with the bridge category and with having ≥1 STI/HIV, respectively. Results: Half of the clients approached refused participation. Median age was 28.9 years; 57.7% had a regular partner, of whom 10.1% had concurrent non-commercial partnerships. Consistent condom use with FSW and regular partners was 72.5% and 17.1%, respectively. The main reason for not using condoms was trust (49.5%). Approximately 18% formed a bridge, and 40.0% a potential bridge. Among those who provided samples (70.5% a blood sample and 89.7% urine sample), prevalence of HIV, syphilis, gonorrhoea, chlamydia, and herpes simplex virus 2 was 1.5%, 1.0%, 0.8%, 5.5%, and 3.4%, respectively. Unprotected sex with FSWs and drug use just before sex were risk factors for having any STI (9.8% of participants). Bridge clients were significantly less educated, more employed, paid lower prices to the FSW just visited, and had a previous STI. Conclusions: Clients showed high-risk sexual behaviour, a relatively high prevalence of HIV in clients compared to national estimates and a substantial proportion of them act as a bridge for HIV/STI transmission between FSW and the general population in Escuintla. Given that this is fuelling the current HIV epidemic, preventive interventions addressing this hard-to-reach group are urgently required. A significant challenge is to overcome the difficulty of reaching clients as well as to address the variety of high-risk behaviours among clients by partner type in this setting and take into account traditional concepts of masculinity.